Pharmacoeconomics of long-acting atypical antipsychotics for acutely relapsed chronic schizophrenia in Finland. (1st February 2016) - Einarson, Thomas R.; Pudas, Hanna; Goswami, Pushpendra; van Impe, Kristel; Bereza, Basil G.
Abstract: Background: Atypical long-acting injectable (LAI) antipsychotics are increasingly available for treating chronic schizophrenia in patients chronically non-adherent to prescribed regimens. Few economic studies have compared these products. Purpose: To determine the cost-effectiveness of aripiprazole (ARI-LAI), paliperidone (PP-LAI), olanzapine (OLZ-LAI), and risperidone (RIS-LAI) in patients with chronic schizophrenia in Finland. Methods: A 1-year decision tree model was adapted with guidance from an expert panel. Patients started hospitalized in relapse; those who responded continued treatment, others were switched to secondary drugs, then clozapine in the event of 2nd line failure. Rates of adherence, stable disease, relapse, and hospitalization were taken from pivotal trials, and utilities from published research. Included were direct costs paid by the Finnish Ministry of Health, in 2015 euros. Outcomes included quality-adjusted life-years (QALYs), hospitalization rates, and rates of relapse not requiring hospitalization. Model robustness was assessed using a series of 1-way and multivariate sensitivity analyses. Results: Expected costs were lowest for PP-LAI at 41, 148€, followed by 41, 543€ for ARI-LAI, 42, 067€ for RIS-LAI and 45, 406€ for OLZ-LAI. Respective QALYs were 0.683, 0.671, 0.666, and 0.672. Re-hospitalization rates and non-admitted relapses were 23.6% and 3.9% for PP-LAI, 28.5% and 4.1% for ARI-LAI, 28.8% and 5.0% for RIS-LAI, 28.3% and 5.2% for OLZ-LAI. PP-LAI treatment was associated with the most days with stable disease (132.0), followed by OLZ-LAI (125.5), ARI-LAI (122.6), and RIS-LAI (114.4). Sensitive inputs between PP-LAI and ARI-LAI included rates of adherence, dropouts, and relapses plus drug prices; dropout and relapse rates for RIS-LAI; OLZ-LAI results were insensitive. In probability sensitivity analyses, PP-LAI dominated ARI-LAI in 75.8% of the 10, 000 iterations, RIS-LAI in 83.1% and OLZ-LAI in 95.7%. Conclusions: PP-LAI dominated the other atypicals. It appears to be the preferred option for treating chronic relapsing schizophrenia.